Tekrarlayan Yedi Gebelik Kaybı Sonrası Başarılı Gebelik: Olgu Sunumu - Nazik, Hakan; Narin, Raziye; Api, Murat; Aytan, Hakan; Gül, Şule; Adıgüzel, Cevdet (Fırat University, 2012)
Tekrarlayan gebelik kayıpları (TGK) reprodüktif çağdaki kadınların yaklaşık %0.5-1'ini etkileyen önemli bir obstetrik problemdir. Etiyolojide birçok hastalık sorumlu tutulsa da vakaların %50-70 inde herhangi bir neden ortaya konulamamaktadır. Açıklanamayan TGK olgularında psikolojik destek verilmesi, haftalık ultrasonlarla yakın izlem ile ilgili yapılan çalışmalarda gebelik kaybı 2-4 kez daha azalmış olarak bildirilmiştir. Bu çalışmada yedi TGK ve multipl risk faktörleri olan bir olgunun başarılı gebeliği sunulmuştur.

Recurrent pregnancy loss (RPL) is an important obstetric problem affecting about 0.5-1% of women in their reproductive period. Although many etiologic factors have been thought to be responsible, in 50-70% of cases no definitive factors can be found. In studies that assess unexplained RPL cases, providing psyhological support and close follow-up with weekly ultrasonography have been reported to decrease pregnancy losses up to 2-4 times. In this study a successful pregnancy following recurrent seven pregnancy losses in a woman with multiple risk factors is presented.
A Successful Pregnancy Following Recurrent Seven Pregnancy Lossess: A Case Report